2021
DOI: 10.1016/j.cegh.2021.100840
|View full text |Cite
|
Sign up to set email alerts
|

Smokeless tobacco use among women in northeastern states, India: A study of spatial clustering and its determinants using National Family Health Survey-4 data

Abstract: Background: Use of tobacco, especially smokeless tobacco have characterised as highly prevalent among women, and also the mode of using smokeless tobacco varies based on geographic location, ingredient availability, cultural/societal norms, and personal preferences. Therefore, this study examines the prevalence and social determinants of use of smokeless tobacco among women in NE India. Further, it also identifies the cluster and district hotspots of smokeless tobacco prevalence. Methods: We analysed a nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Our results are supported by data on state wise prevalence of tobacco use in India, which indicates high prevalence of tobacco in states from these regions, that is much greater than the national average [50][51][52]. Studies have also reported greater use among students, women and tribal population in this region [53][54][55][56]. There have been studies that have highlighted that wealth quintile is an important factor that affects tobacco use [57,58].…”
Section: Discussionsupporting
confidence: 82%
“…Our results are supported by data on state wise prevalence of tobacco use in India, which indicates high prevalence of tobacco in states from these regions, that is much greater than the national average [50][51][52]. Studies have also reported greater use among students, women and tribal population in this region [53][54][55][56]. There have been studies that have highlighted that wealth quintile is an important factor that affects tobacco use [57,58].…”
Section: Discussionsupporting
confidence: 82%
“…Despite the deleterious effects of SLT products on women’s health, an increase in use is observed across all age groups of women in Assam, Arunachal Pradesh, Manipur, Tripura and Nagaland. Cultural practices and norms 10 , 15 , higher prevalence of any form of tobacco in the region 16 and unregulated market particularly for unpackaged tobacco 17 could be the reasons for increased prevalence of use among women in these States. While an effective NTCP may have contributed to the overall reductions in the use of SLT 1 , findings necessitate deliberate inclusion of gender-sensitive tobacco control messages and campaigns in the NE States’ tobacco control programmes for prevention of tobacco use among women 6 , 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In India, the world’s second-largest tobacco consumer, where predominantly STPs are used extensively by > 200 million people and STPs act as a putative causative factor of various cancers [80] , [81] . Some states of NEI have the highest prevalence of STPs use such as Mizoram has the highest prevalence of STPs use (47.8 ± 1.2) followed by Manipur among females (46.1 ± 0.7) (by National Family Health Survey-4, NFHS-4) [82] . Most popular STPs include khaini, gutkha, zarda, paan or BQ with tobacco, loose tobacco leaf or sadapata, tuibur or hidakphu [81] .…”
Section: Genetic Instability Due To Smokeless Tobacco Products Usementioning
confidence: 99%